Comprehensive analysis of human endogenous retrovirus transcriptional activity in human tissues with a retrovirus-specific microarray - Seifarth, Wolfgang; Frank, Oliver; Zeilfelder, Udo; Spiess, Birgit; Greenwood, Alex D.; Hehlmann, Rüdiger; Leib-Mösch, Christine (Journal of virology, 2005)
Retrovirus-likesequences account for 8 to 9% of the human genome. Among thesesequences, about 8,000 pol-containing proviral elements havebeen identified to date. As part of our ongoing search for active andpossibly disease-relevant human endogenous retroviruses (HERVs), wehave recently developed an oligonucleotide-based microarray. The assayallows for both the detection and the identification of most knownretroviral reverse transcriptase (RT)-related nucleic acids inbiological samples. In the present study, we have investigated thetranscriptional activity of representative members of 20 HERV familiesin 19 different normal human tissues. Qualitative evaluation of chiphybridization signals and quantitative analysis by real-time RT-PCRrevealed distinct HERV activity in the human tissues underinvestigation, suggesting that HERV elements are active in human cellsin a tissue-specific manner. Most active members of HERV families werefound in mRNA prepared from skin, thyroid gland, placenta, and tissuesof reproductive organs. In contrast, only few active HERVs weredetectable in muscle cells. Human tissues that lack HERV transcriptioncould not be found, confirming that human endogenous retroviruses arepermanent components of the human transcriptome. Distinct activitypatterns may reflect the characteristics of the regulatory machinery inthese cells, e.g., cell type-dependent occurrence of transcriptionalregulatoryfactors.
Gesehen am 11.05.2022